MULTISCALE MODELING OF FLUID-STRUCTURE INTERACTION IN WIND TURBINE BLADES TO IMPROVE ENERGY CONVERSION EFFICIENCY IN RENEWABLE SYSTEMS - Kaito Tanaka; Sulaiman Sulaiman; Lars Jensen (Yayasan Adra Karima Hubbi, 2026)
The increasing demand for renewable electricity drives the need to improve wind turbine efficiency under complex aerodynamic and structural conditions. Numerical approaches often separate airflow analysis and structural response, thus reducing the accuracy of predicting aeroelastic behavior. This study aims to analyze the effectiveness of multiscale fluid-structure interaction (FSI) modeling in improving wind turbine blade performance through integrated aerodynamic, structural, and material analysis. Using a mixed-method sequential explanatory design, the study tested 2,800 simulation scenarios on 48 blade configurations under varying wind speeds, turbulence intensities, and composite material properties. Quantitative analysis included multivariate statistics and hierarchical regression, while qualitative thematic analysis was drawn from expert interviews and engineering workshops. Results show that a fully coupled multiscale FSI model consistently outperforms conventional approaches in improving aerodynamic efficiency, computational convergence, structural stability, vibration damping, and fatigue life prediction. Composite material optimization enhanced structural robustness under dynamic conditions. This framework provides practical guidance for designers and engineers to optimize renewable energy conversion through advanced multiphysics simulations.